ANALISIS PERKEMBANGAN UMKM MENURUT PANDANGAN IBNU KHALDUN TERHADAP KEMAJUAN PEREKONOMIAN ISLAM INDONESIA - fathorrahman (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2021)
The development of MSMEs is currently a driving force foreconomic growth in lndonesia, this can be seen from theincreasing number of MSME actors who open businessesthrough social media pages. The economic empowermentprogram for Muslims is also being developed by thegovernment and is expected to be implemented well. Theresearch method used is descriptive qualitative based onevents, and social conditions in the community. Thepurpose of this study is to analyze the progress of MSMEstowards the Islamic economy in lndonesia. The results ofthe study show that MSMEs play an important role in theprogress of the Islamic economy in Indonesia.